Emerging trends in advanced science : selected, peer reviewed papers from the International Conference on Emerging Trends in Science, Engineering and Technology (ICETSET-2014), April 18-19, 2014, Chennai, India - Sathi, Rama Reddy (Applied mechanics and materials ;, 2014)
This journal consists of collection of selected, peer reviewed papers from the International Conference on Emerging Trends in Science, Engineering and Technology (ICETSET-2014) held during 18th and 19th April 2014 at Jerusalem College of Engineering, Chennai. ICETSET-2014 explores the art of designing systems in arriving at a Smart, Sustainable and Secured Technology. The conference aims at bringing together experts, practitioners, academicians, researchers and students to meet the following objectives. Develop a forum towards smart, sustainable and secured technology. Promote the development of a supportive community of experts and a spirit of collaborative research. Provide a supportive setting for feedback on current research and guidance on future research directions. To strengthen Industry-Institute interaction ties and lay foundation for engineering a better world. Keyword: Asymmetric Cascaded Multilevel Inverter; Data Warehouse; Enhanced Back; propagation Algorithm; Fuzzy Controllers; Grid Connected Inverter; Induction Heating; Micro-Wind Power Generation System; Self-Lift Positive Output p/o Luo Editors Sathi, Venkatesan, Nagarajan, and Natesan present students, academics, researchers, and professionals in a variety of fields with a selection of peer-reviewed papers from the materials presented at the International Conference on Emerging Trends in Science, Engineering, and Technology, held in Chennai India in the Spring of 2014. The twenty-eight contributions selected by the editors include papers on building multi-dimensional cubes to analyze public examination results, comparative analysis of various modulation strategies for induction heating systems, the ductility of concrete-encased cold-formed steel beams with trapezoidally corrugated webs, and a great variety of other subjects. -- Applied science-- Engineering-- Technology management.